A reference constructicon as a database - Patel, Malin; Garibyan, Armine; Winckel, Elodie; Evert, Stephanie (Yearbook of the German Cognitive Linguistics Association, 2023)
This article explores the importance of database architecture in building a reference constructicon. Several reference constructicons have been implemented for various languages (FrameNet Constructicon, English Constructicon, Japanese FrameNet Constructicon, German Constructicon, Swedish Constructicon, FrameNet Brasil Constructicon, Russian Constructicon). However, most constructicon projects do not provide explicit information about their implementation or the underlying data model. A recent reference constructicon project dealing mainly with the English language is CASA (Construction Grammar Approach to Syntactic Analysis). In this paper, we present the data model underlying CASA in detail and its current implementation as a relational database and web interface. Relational databases are widely used for many different applications and allow large amounts of data to be stored and managed in a structured and efficient way.<br
Keywords: constructicon; database; Construction Grammar; constructicography; implementation